2022
DOI: 10.1177/21676968221110541
|View full text |Cite
|
Sign up to set email alerts
|

Finances and Fate: Parent Financial Socialization, Locus of Control, and Mental Health in Emerging Adulthood

Abstract: Utilizing a sample of 4182 U.S. emerging adults and structural equation modeling, we examined how parent financial socialization received during childhood and adolescence is associated with mental health in emerging adulthood and whether locus of control is an intervening variable. Financial socialization was negatively associated with anxiety and depressive symptoms, and positively associated with life satisfaction. Indirect pathways were found through locus of control. That is, emerging adults who had receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
5
0
1
Order By: Relevance
“…Parental financial socialization includes (a) discussion—verbal communication, (b) modeling—setting behavioral examples, and (c) experiential learning—using life experiences to help offspring internalize rules, norms, and knowledge (LeBaron et al, 2018; LeBaron‐Black, Curran, et al, 2022; LeBaron‐Black, Li, et al, 2022). Parental financial socialization helped individuals develop financial behaviors during childhood and adolescence, which—while controlling for possible predictors such as employment, personal income, personal education, stable personalities, and family income—can cause a long‐lasting and substantial impact on individuals' well‐being (Dew & Xiao, 2011; Goyal & Kumar, 2021; Gudmunson & Danes, 2011; Li et al, 2020; Li et al, 2022; Sorgente & Lanz, 2017).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Parental financial socialization includes (a) discussion—verbal communication, (b) modeling—setting behavioral examples, and (c) experiential learning—using life experiences to help offspring internalize rules, norms, and knowledge (LeBaron et al, 2018; LeBaron‐Black, Curran, et al, 2022; LeBaron‐Black, Li, et al, 2022). Parental financial socialization helped individuals develop financial behaviors during childhood and adolescence, which—while controlling for possible predictors such as employment, personal income, personal education, stable personalities, and family income—can cause a long‐lasting and substantial impact on individuals' well‐being (Dew & Xiao, 2011; Goyal & Kumar, 2021; Gudmunson & Danes, 2011; Li et al, 2020; Li et al, 2022; Sorgente & Lanz, 2017).…”
Section: Figurementioning
confidence: 99%
“…Taking together theory and empirical studies, a mediational process is proposed that parental financial socialization is associated with young adults' well-being via financial behaviors (i.e., parental financial socialization à financial behaviors à well-being; Gudmunson & Danes, 2011;LeBaron-Black, Li, et al, 2022;Li et al, 2020;Li et al, 2022;Li et al, 2019). Because the economic world is getting increasingly complicated by social changes such as the COVID-19 pandemic (Kelley et al, 2023;Sun et al, 2021), drawing from family financial socialization theory and empirical studies to test the mediational process is important for preparing the younger generation for a better future.…”
mentioning
confidence: 99%
“…Additionally, future research could investigate the specific financial behavior that mediate the relationship between family financial socialization and life satisfaction. Third, the current study mainly focuses on the influence of direct parental teaching; however, LeBaron-Black et al (2022) show that parent financial modeling (children learn by observing) is also associated with financial behaviors and financial satisfaction. Therefore, future studies may examine the association between indirect parent financial socialization and life outcomes.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 89%
“…For example, Serido et al (2010) finds that the quality of communication between parents and children on financial topics is the strongest predictor of children's financial, psychological and personal well-being. Moreover, research also indicated that parental financial socialization received during childhood and adolescence is helpful for combating anxiety and depressive symptoms, thus positively associated with financial satisfaction and life satisfaction (Allsop et al, 2021;LeBaron-Black et al, 2022). Based on the above literature, the following hypothesis is proposed: H1.…”
Section: The Relationship Between Parental Direct Teaching Financial ...mentioning
confidence: 99%
See 1 more Smart Citation